Optimization and authentication using XTEA for low power hardware encryption for secure RFID - Kasorn Galajit; Afzulpurkar, Nitin V.; Pasin Israsena; Chumnarn Panyasai; National Science and Technology Development Agency (NSTDA); Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
This study describes an Extended Tiny Encryption Algorithm (XTEA) to implement on FRID and optimization of the hardware implementation for area, timing and Power. XTEA was applied with hash algorithm to do authorization and data integrity due to security and privacy concern in secure RFID system The objective of the study is to design the module and implement on hardware to do encryption function, also optimization for area constrain. The additional feature which is extended from the generic module of encryption is authorization function and data integrity. The multiple designs are made to compare the best solutions to meet the system requirement. VHDL source codes are designed then simulate and verify, then implement on real hardware to test function and performance of designs. The results show that the proposed algorithm performs well on encryption function and authorization. Results from multiple designs show the trade off between area, timing and power requirement in each system. The design of XTEA based hash algorithm using one XTEA unit meets the requirement of the secure RFID system
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Microelectronics, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2007
Keywords: Radio frequency identification systems